Reaction mechanism of atomic layer deposition of zirconium oxide using zirconium precursors bearing amino ligands and water - Xu, Rui; Zhou, Zhongchao; Li, Jing; Zhang, Xu; Zhu, Yuanyuan; Xiao, Hongping; Xu, Lina; Ding, Yihong; Li, Aidong; Fang, Guoyong (Frontiers in Chemistry, 2022)
As a unique nanofabrication technology, atomic layer deposition (ALD) has been widely used for the preparation of various materials in the fields of microelectronics, energy and catalysis. As a high-κ gate dielectric to replace SiO2, zirconium oxide (ZrO2) has been prepared through the ALD method for microelectronic devices. In this work, through density functional theory calculations, the possible reaction pathways of ZrO2 ALD using tetrakis(dimethylamino)zirconium (TDMAZ) and water as the precursors were explored. The whole ZrO2 ALD reaction could be divided into two sequential reactions, TDMAZ and H2O reactions. In the TDMAZ reaction on the hydroxylated surface, the dimethylamino group of TDMAZ could be directly eliminated by substitution and ligand exchange reactions with the hydroxyl group on the surface to form dimethylamine (HN(CH3)2). In the H2O reaction with the aminated surface, the reaction process is much more complex than the TDMAZ reaction. These reactions mainly include ligand exchange reactions between the dimethylamino group of TDMAZ and H2O and coupling reactions for the formation of the bridged products and the by-product of H2O or HN(CH3)2. These insights into surface reaction mechanism of ZrO2 ALD can provide theoretical guidance for the precursor design and improving ALD preparation of other oxides and zirconium compounds, which are based ALD reaction mechanism.